The Link Between Teacher Emotional Regulation and Maladaptive Behavior of Pre-School Student - Uswatun Hasanah; Widyastuti Widyastuti (Psycho Idea, 2023)
Maladaptive behavior often appears in preschool-aged children as form of child adjustment to wider social environment. Maladaptive behavior that is not managed early on will have negative impact on child development. Intervention is needed so that maladaptive behavior is not attached to the child's character. Teachers are social agents who play an important role in changing children's behavior, high teacher emotional regulation is needed to weaken children's maladaptive behavior . This study aims to determine the link between teacher emotional regulation and maladaptive behavior of preschoolers. This research is correlational quantitative research. The data collection technique used questionnaire using Emotional Regulation Questionnare scale with reliability of 0.783 and Strength and Difficulty scale with reliability of 0.756. The subjects of this study were 200 ‘Aisyiyah Sidoarjo KB/TK teachers. The sampling technique uses quota sampling technique and data analysis uses Spearman Rho Correlation. The results of this study indicate the value of the correlation coefficient r = -0.54 with significance value of 0.001 (P <0.05). This shows that there is negative link between teacher emotional regulation and maladaptive behavior of pre-school in 'Aisyiyah Sidoarjo KB/TK students. The higher the teacher's emotional regulation, the lower the maladaptive behavior raised by 'Aisyiyah Sidoarjo KB/TK students.